Rare case of broad ligament pregnancy - Ojha, Pragya; Vaish, Kalika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Broad ligament pregnancy is rare form of abdominal pregnancy. There is high risk of maternal morbidity and mortality. Due to its rarity, usually, diagnosis cannot be established before surgery. We reported a 27 year old, G3P2L2 who presented with 4 month amenorrhea with pain in lower abdomen. Ultrasonography revealed a single live extra-uterine pregnancy of 17 weeks in right adnexa. A right sided Broad ligament pregnancy was found on exploratory laparotomy. Excision of mass with right sided salpingo-oophrectomy was performed. Post operative course was uneventful. Early diagnosis with high risk of suspicion and early intervention is needed to overcome it’s related complications.